2017
DOI: 10.1080/19390211.2017.1334736
|View full text |Cite
|
Sign up to set email alerts
|

High Dose Vitamin D Supplementation Is Associated With a Reduction in Depression Score Among Adolescent Girls: A Nine-Week Follow-Up Study

Abstract: Although vitamin D deficiency is known to be a risk factor for some psychological disorders, there have been few studies on the effects of vitamin D supplementation on their symptoms. Depression and aggression are common mental disorders and are associated with disability and disease burden. We aimed to evaluate the effectiveness of high-dose vitamin D supplementation on depression and aggression scores in adolescent girls. Nine hundred forty adolescent girls received vitamin D at a dose of 50,000 IU/week for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 34 publications
1
41
0
2
Order By: Relevance
“…Biochemical factors including serum serum calcium (Ca),and phosphate (P), , fasting blood glucose (FBG), creatinie, blood urea nitrogen (BUN) and lipid profile; total cholesterol (TC), triglyceride (TG), and high-density lipoprotein cholesterol (HDL-C), measured by using commercial kits (Pars Azmun, Karaj, Iran) and the BT-3000 auto-analyzer (Biotechnica, Rome, Italy). Lowdensity lipoprotein cholesterol (LDL-C) was estimated using Friedewald formula if serum TGs concentrations < 4.52 mmol/L [29][30][31]. High sensitivity C-reactive protein (Hs-CRP) was quantified using an immunoturbidimetry method, with limit of detection (LoD) 0.06 mg/L (Biosystems, Spain).…”
Section: Anthropometric and Biochemical Measurementsmentioning
confidence: 99%
“…Biochemical factors including serum serum calcium (Ca),and phosphate (P), , fasting blood glucose (FBG), creatinie, blood urea nitrogen (BUN) and lipid profile; total cholesterol (TC), triglyceride (TG), and high-density lipoprotein cholesterol (HDL-C), measured by using commercial kits (Pars Azmun, Karaj, Iran) and the BT-3000 auto-analyzer (Biotechnica, Rome, Italy). Lowdensity lipoprotein cholesterol (LDL-C) was estimated using Friedewald formula if serum TGs concentrations < 4.52 mmol/L [29][30][31]. High sensitivity C-reactive protein (Hs-CRP) was quantified using an immunoturbidimetry method, with limit of detection (LoD) 0.06 mg/L (Biosystems, Spain).…”
Section: Anthropometric and Biochemical Measurementsmentioning
confidence: 99%
“…Although a recent uncontrolled intervention study in 940 Iranian adolescent girls showed a significant reduction in depression scores after 9 weeks of vitamin D supplementation [15], randomized controlled trials (RCTs) examining the antidepressant effect of vitamin D supplementation have not been conducted to date in children and adolescents. In adults, systematic reviews and meta-analyses of existing RCTs revealed conflicting results which might be explained by limitations in the study design of the included RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported a strong relationship between vitamin D status and different health outcomes (Bahrami et al, ; McCullough, Bostick, & Mayo, ; Tabatabaeizadeh et al, ). Attention has now turned to the gene‐environment interactions that could have an impact on various vitamin D‐related disorders (Ahn et al, ; Dickinson et al, ).…”
Section: Introductionmentioning
confidence: 99%